Exploration of Entrepreneur’s Challenges to Cope with Nepalese Tourism Market Dynamics - Bhattarai, Bal Ram; Prompanyo, Manoch (Janapriya Journal of Interdisciplinary Studies, 2021)
Change is inevitable in every sphere of human life; tourism activities are rapidly changing than other activities. The Nepalese tourism industry has also brought changes in different aspects, how those changes are perceived by the entrepreneurs of the industry is the main concern of the study. The primary objective of this study is to explore the dimensions of tourism market dynamics and entrepreneur’s readiness to cope with the perceived challenges. A qualitative framework has been adopted of an in-depth interview with leading entrepreneurial personalities of the tourism industry of Nepal. Representing hospitality, catering, trekking, and travel with at least 20 years of experience in tourism-related activities are considered as the true representation to collect primary data. Manual thematic content analysis has been employed to generate the theme of the interview. Major changes in customer expectation because of the market shift, technological advancement but not appropriate application, lacking experienced trained human resources, and travel-related inconvenience are the major challenges for tourism entrepreneurs of Nepal.